Keyword++: A Framework to Improve Keyword Search Over Entity Databases - Ganti, Venkatesh; He, Yeye; Xin, Dong (Proceedings of International Conference on Very Large Databases (VLDB), 2010)
Keyword search over entity databases (e.g., product, movie databases) is an important problem. Current techniques for keyword search on databases may often return incomplete and imprecise results. On the one hand, they either require that relevant entities contain all (or most) of the query keywords, or that relevant entities and the query keywords occur together in several documents from a known collection. Neither of these requirements may be satisfied for a number of user queries. Hence results for such queries are likely to be incomplete in that highly relevant entities may not be returned. On the other hand, although some returned entities contain all (or most) of the query keywords, the intention of the keywords in the query could be different from that in the entities. Therefore, the results could also be imprecise. To remedy this problem, in this paper, we propose a general framework that can improve an existing search interface by translating a keyword query to a structured query. Specifically, we leverage the keyword to attribute value associations discovered in the results returned by the original search interface. We show empirically that the translated structured queries alleviate the above problems.